EXAMINING THE EFFICACY OF REPETITION AND PRACTICE EXERCISES IN FOREIGN LANGUAGE VOCABULARY LEARNING (CAHIERS MAGELLANES-NS, 2024)
This article explores various methods and factors involved in the formation of foreign language lexical skills during the teaching of foreign languages. It discusses different approaches to vocabulary acquisition, including traditional methods like vocabulary lists and innovative techniques such as contextual learning and word formation strategies. Additionally, it examines various factors that influence the development of lexical skills, such as frequency of exposure, relevance to context, individual learning styles, and cultural background. By understanding these methods and factors, language educators can enhance their teaching practices and support students in acquiring robust lexical skills.